Should Korea Worry about a Permanently Weak Yen? - Ree, Jack.; Choi, Seoeun; Hong, Gee Hee. (Washington, D.C. : International Monetary Fund, 2015)
Three years have passed since the Bank of Japan's asset purchase program was introduced in 2011, causing a sharp decline in the value of the Japanese Yen. What would be the implications for Japan and Korea's exporters if the weak Yen is here to stay? We explore this question by examining exporters' pricing behaviors and volume responses to exchange rate shocks. We find that if the weak Yen persists, it would strengthen Japan's price competitiveness over time as export prices respond with a lag. We also find that while direct boosts to export demand will be rather limited, a persistently weaker Yen would expand the Japanese exporters' profits lastingly, which could reinvigorate the ability, particularly of flagship exporting firms, to compete and grow in the global market over time. These findings suggest that the muted price and volume response so far to the sustained weakness of the Yen may mask a more fundamental shift in the relative competitiveness of Japanese and Korean exporters.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet